EFISIENSI PERANAN APARATUR PEMERINTAH KECAMATAN DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI BATUPUTIH SUMENEP - Eka Saputra, Mohammad Ardiansyah; Muchsin, Slamet; Kurniati, Rini Rahayu (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The aim of this research is to determine the efficiency of the role of sub-district government officials in population administration services in Batuputih Sumenep, as well as the factors that influence their role in improving population administration services. This research combines qualitative strategies with descriptive research design. The research location is in Batuputih District, Sumenep Regency. For this research, the research methods used include document study, interviews, and observations between January and February 2023. The analysis paradigm according to (Matthew B. Miles 2014), which involves data collection, data presentation, conclusion drawing, and verification, was used for the data analysis in this research. The results show the efficiency of the role of sub-district government officials in population administration services in Batuputih Sumenep. A good level of efficiency and achievement is demonstrated by the completeness of correspondence and management services. The inhibiting factors include the budget being disbursed in stages and the lack of human resources at the Batuputih Regency Population and Civil Registration Department which makes implementing standards more difficult. Supporting factors show that the government is still trying to develop and provide service standards using contemporary media, which is one of the supports for the efficiency of the role of the apparatus to help achieve good service quality.